Youth-centred swimming: a matter of policy and pedagogy - de Martelaer, K.; De Knop, P.; Theebom, M.; Harthoorn, S. (Biomechanics and Medicine in Swimming VIII, 1999)
As the programme in sport clubs in general and in the Flemish swimming clubs in particular is organised and guided by adults, it remains unclear whether sport is adapted to the wishes and expectations of youngsters themselves. A qualitative research provided a complete picture of what is important to young swimmers, their coaches and parents and gave the opportunity to concretise "youth-centred organised swimming". Data were gathered by means of triangulation: written material, half structured interviews and participant observation. The inductive data analysis of this qualitative research resulted in four major categories: (a) nature and organisation of activities, (b) guidance and policy, (c) feelings and behaviour, (d) swimming as a leisure time activity. In a second part, the results of a SWOT -analysis (strengths, weaknesses, opportunities and threats) of organised swimming are analysed. The concern for an "in depth" focus on age group swimmers' activities in combination with a policy oriented research among members of the board resulted in a set of recommendations. These recommendations are a scientific basis for a profound discussion concerning matters of policy and pedagogy in age group swimming.